2004
DOI: 10.1002/chem.200400641
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Adducts of the Side‐On End‐On Dinitrogen‐Bridged Complex [{(NPN)Ta}2(μ‐H)2(μ‐η12‐N2)] with AlMe3, GaMe3, and B(C6F5)3: Synthesis, Structure, and Spectroscopic Properties

Abstract: Reaction of the side-on end-on dinitrogen complex [{(NPN)Ta}(2)(mu-H)(2)(mu-eta(1):eta(2)-N(2))] (1; in which NPN=(PhNSiMe(2)CH(2))(2)PPh), with the Lewis acids XR(3) results in the adducts [{(NPN)Ta}(2)(mu-H)(2)(mu-eta(1):eta(2)-NNXR(3))], XR(3)=GaMe(3) (2), AlMe(3) (3), and B(C(6)F(5))(3) (4). The solid-state molecular structures of 2, 3, and 4 demonstrate that the N-N bond length increases relative to those found in 1 by 0.036, 0.043, and 0.073 A, respectively. In solution complexes 2-4 are fluxional as evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 40 publications
4
34
0
Order By: Relevance
“…[10] The NÀN stretching frequencies of these dinuclear complexes were determined to be around 1150 cm À1 , [11] similar to that reported here. The [GdGdNN] and [Gd 2 (m-NN)] isomers with terminal and bridging N 2 ligands were also calculated, but they are 55.6 and 34.9 kcal mol À1 higher in energy than (2.0 km mol À1 ), respectively.…”
supporting
confidence: 83%
“…[10] The NÀN stretching frequencies of these dinuclear complexes were determined to be around 1150 cm À1 , [11] similar to that reported here. The [GdGdNN] and [Gd 2 (m-NN)] isomers with terminal and bridging N 2 ligands were also calculated, but they are 55.6 and 34.9 kcal mol À1 higher in energy than (2.0 km mol À1 ), respectively.…”
supporting
confidence: 83%
“…11 Theoretical studies are in progress to clarify the nature of 6 and the general mechanism accounting for the intriguing single and double P-P coupling between dppm and activated P 4 . 12 In summary, we have shown that bimetallic cooperativity is relevant to promote P 4 activation and to govern the activation products as for the recent reports in N 13 2 and P 10 4 chemistry. Complexes 4 and 5 represent a new bonding mode for a metal-activated P 4 ligand featuring an unprecedented pentaphosphorus moiety resulting from the intramolecular coupling of the metal-activated P 4 -tetrahedron with a Downloaded by [Simon Fraser University] at 13:30 18 November 2014 neighbouring nucleophilic dppm ligand.…”
Section: Methodssupporting
confidence: 71%
“…As shown in Scheme 17, the exposed nitrogen of the side-on end-on N 2 unit forms adducts with a variety of simple Lewis acids [77]. Specifically, trimethylaluminum (17.…”
Section: Tantalummentioning
confidence: 99%